Cover Picture: Source of Selectivity in Oxidative Cross‐Coupling of Aryls by Solvent Effect of 1, 1, 1, 3, 3, 3‐Hexafluoropropan‐2‐ol (Chem. Eur. J. 35/2015). Issue 35 (18th August 2015) - Elsler, Bernd; Wiebe, Anton; Schollmeyer, Dieter; Dyballa, Katrin M.; Franke, Robert; Waldvogel, Siegfried R.
Abstract : Precisely adjusted solvates. influence the oxidation potential of substrates for the electrochemical cross‐coupling of arenes. The solvent mixture based on 1, 1, 1, 3, 3, 3‐hexafluoroisopropanol (HFIP) and MeOH gives rise to a decoupling of nucleophilicity from the oxidation potential. In their Full Paper onpage 12321 ff., S. R. Waldvogel and co‐authors rationalize the outstanding selectivity of the anodic cross‐coupling. This solvent effect explains also the selectivity previously found by HFIP mixtures.